2017
DOI: 10.18632/oncotarget.21921
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriome and mycobiome associations in oral tongue cancer

Abstract: Squamous cell carcinoma of the oral (mobile) tongue (OMTC), a non-human papilloma virus-associated oral cancer, is rapidly increasing without clear etiology. Poor oral hygiene has been associated with oral cancers, suggesting that oral bacteriome (bacterial community) and mycobiome (fungal community) could play a role. While the bacteriome is increasingly recognized as an active participant in health, the role of the mycobiome has not been studied in OMTC. Tissue DNA was extracted from 39 paired tumor and adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 53 publications
(51 reference statements)
5
94
1
3
Order By: Relevance
“…() and Mukherjee et al. () found that Streptococcus was significantly enriched in OSCC, whereas Al‐Hebshi et al. () found this genus to be significantly enriched in the controls.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…() and Mukherjee et al. () found that Streptococcus was significantly enriched in OSCC, whereas Al‐Hebshi et al. () found this genus to be significantly enriched in the controls.…”
Section: Resultsmentioning
confidence: 97%
“…Twenty‐three non‐specific sequence‐based identification studies of the microbiota were included, 14 of which were published in 2017–2018 (Table ) (Al‐Hebshi, Nasher, Idris, & Chen, ; Al‐Hebshi et al., ; Bebek et al., ; Börnigen et al., ; Guerrero‐Preston et al., , ; Hayes et al., ; Hooper et al., ; Hu, Zhang, Hua, & Chen, ; Lee et al., ; Li et al., ; Mukherjee et al., ; Perera et al., , ; Pushalkar et al., , ; Schmidt et al., ; Shin et al., ; Wang et al., ; Wolf et al., ;Yang, Huang et al., ; Yang, Yeh et al., ; Zhao et al., ). Twenty‐one studies focused on bacterial identification (all by 16S rRNA gene regions), one of which also identified fungi (ITS2 gene fragment), one only fungi, and one was restricted to viral identification (human rRNA detection followed by search for viral sequences).…”
Section: Resultsmentioning
confidence: 99%
“…The microbiome findings have been varied. One group reported decrease (Schmidt et al., ), while two other groups reported increase (Guerrero‐Preston et al., ; Mukherjee et al., ) of Streptococcus species in oral cancer lesions in comparison with controls. We think that microbial cancer‐promoting factors might not be limited to specific bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of these datasets has been the catalyst for a number of studies investigating the importance of fungi within oral biofilm infections. This has fuelled the concept of interkingdom communities, which continues to grow above and beyond our traditional viewpoint of bacterial-bacterial interactions [12][13][14]. Indeed, the advancement in sequencing technologies has facilitated the characterisation of the fungal oral microbiome [11, 15•, 16].…”
Section: Introductionmentioning
confidence: 99%